Hypersensitivity Reactions to Vaccines: Current Evidence and Standards for SARS-CoV-2 Vaccines - Carvalho, Jóni Costa (2021)
The first reports of hypersensitivity reactions following the rollout of COVID-19 vaccination programs have raised public concern. Given the recent availability and novel mechanisms of COVID-19 vaccines, there is limited data on possible hypersensitivity reactions. Although it seems rare, the incidence of anaphylaxis for approved COVID-19 vaccines has been suggested as being higher when compared to previous vaccines. Adequate risk assessment, recognition, classification, and management of hypersensitivity reactions is crucial to ensure safe immunization and avoid misinformation and vaccine hesitancy. In this review, we present an overview of the types of hypersensitivity reactions that can potentially occur due to vaccination and the possible allergenic components of COVID-19 vaccines, as well as a suggestion for causality and risk assessment for the BNT162b2, mRNA-1273 and AZD1222 vaccines.